2009
DOI: 10.1007/s10310-009-0151-7
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of stand structure and tree species diversity in subtropical forest degraded by clear logging

Abstract: Subtropical forests in the Ryukyu Islands have been degraded by silvicultural practices, and thus their structural attributes are being shifted to other states dominated by a few tree species. This study clarified the mechanisms of the change, and examined the effect of clear logging on the resilience of a subtropical forest. Sprouting regeneration and typhoon disturbance were introduced into an individual-based model, SEIB-DGVM, for describing stand development and succession. The regeneration dynamics from y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…The differences in the community weighted mean for a functional trait between forest types with different management histories is informative for considering the shifts of the dominant trait value in a community (Baraloto et al 2012). Greater leaf thickness and wood density found in managed forests suggest that clear-cutting and plantation establishment may have affected growth dynamics in the forests (Fujii et al 2009). Forest practices often promote the dominance of pioneer species with low wood density and high specific leaf area and leaf nitrogen concentration (Baraloto et al 2012, Carreño-Rocabado et al 2012, but the subtropical forest demonstrated a converse trend.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in the community weighted mean for a functional trait between forest types with different management histories is informative for considering the shifts of the dominant trait value in a community (Baraloto et al 2012). Greater leaf thickness and wood density found in managed forests suggest that clear-cutting and plantation establishment may have affected growth dynamics in the forests (Fujii et al 2009). Forest practices often promote the dominance of pioneer species with low wood density and high specific leaf area and leaf nitrogen concentration (Baraloto et al 2012, Carreño-Rocabado et al 2012, but the subtropical forest demonstrated a converse trend.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 46 tree species with different subtropical forest ecological niches were considered in describing the stand development processes (Fujii et al 2009). Species traits were characterized in terms of the maximum tree height, maximum crown width, wood density, and sprouting rate.…”
Section: Model Developmentmentioning
confidence: 99%
“…At the end of the simulation period, the impacts of the cutting cycle on tree species richness, the dominance of Castanopsis sieboldii and tree species diversity was quantified. We focused on the dynamics of C. sieboldii after clearlogging because this species is the most dominant, characterizing the forest structure and dynamics in subtropical forests (Kubota et al 2005;Fujii et al 2009). …”
Section: Logging Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…We applied a spatially explicit individual-based dynamic global vegetation model (SEIB-DGVM) developed by Sato et al (2007). This model takes into account sprouting regeneration and typhoon disturbance, and captures the essential features of stand development, including a selfthinning process that follows the -3/2 power law, as well as the facilitating effect of typhoon disturbance on the coexistence of subordinate species (Fujii et al 2009). This simulation model can quantify the ecological/economical constraints of logging regimes and forest prescriptions, and could provide valuable information on alternative options for forest management (Fujii et al 2010).…”
Section: Introductionmentioning
confidence: 99%